The Use of Diary in Teaching of Writing Recount Texts at SMPN 03 Banjarbaru, South Kalimantan Province - Supiani Supiani (Universitas Cokroaminoto Palopo, 2016)
The objectives of this research is to describe the process of teaching writing recount texts by using diary, to find out the teacher’s problemsand students’ responses toward using diary. The research employs a descriptive qualitative research, in which the instruments come fromobservation, interview and documentation. The subject of this research is an English teacher and 30 students ofthe eight grade of SMPN 03 Banjarbaru in the academic year 2015/2016. Findings show the use of diary in teaching writing recount text could help and develop students’ writing. The teacher explained and instructed in procedural teaching practice to diary usage. However, the problems were limited time at the activities and lack of the teacher’s knowledge. Generally, the use of diary gave a creativity both the teacher and students and made students motivated in learning writing. Thus, diary is one of effective ways to express the students’ ideas in writing because they can tell prior activities or experiences happened.